Finance for the poor in demand: Who uses microfinance and why? - Christiane Ströh de Martínez (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2011)
The paper adds to the debate on how far microfinance can contribute to poverty reduction and development. The recent controversial discussion about microfinance as a development instrument is taken as a starting point. The paper starts with the hypothesis that the prevalent notions and assumptions about the users of microfinance are behind the controversies. Hence, after an analysis of common concepts about microfinance clients and their usage of financial services, a different theoretical frame is presented. From a social science perspective, the frame builds on the distinction of different modes of production within societies and economies as proposed by Structural Heterogeneity. This leads to a different understanding of microenterprises within a family-led mode of production, which is further developed in the light of Schumpeter's analysis of economic development. The proposed theoretical approach is linked to recent empirical research on microfinance users, especially Financial Diary research. From this analysis, a new theoretical conception of the demand side of microfinance emerges. It stresses the relevance of considering different socioeconomic formations people live and work in. For the important family-led mode of production, typical usage patterns point to the need for convenient, flexible, multi-purpose financial management services.
Keywords: 330; Microfinance; Structural Heterogeneity; family-firms; access to finance; poverty reduction